What Effect does FIFA11+ for kids have on the fundamental motor skills of elementary school soccer players? - Nakagawa, Kazumasa; Suto, Yuta; Saito, Ryuta; Iwasaki, Kazuki; Kubo, Kazuki (Journal Physical Therapy UNISA, 2025)
The FIFA 11+ is an established injury prevention warm-up program for players aged 14 years and older, and the FIFA 11+ for Kids (FIFA 11+K) was later developed to support younger players with playful exercises targeting balance, coordination, and strength. While its injury-preventive and performance benefits have been reported, little is known about its effects on fundamental motor skills, which have been declining among Japanese children. This study examined the effects of FIFA 11+K on fundamental motor skills in elementary school boys belonging to a local soccer club. Sixty-six children (8.2 ± 1.5 years) performed FIFA 11+K twice weekly for three months as a warm-up (intervention group), while 28 children (7.2 ± 1.6 years) continued their usual warm-up (control group). Performance in the 50-m sprint, standing long jump, and ball throw, as well as movement quality (5-point observational scale), were assessed before and after the intervention. The intervention group showed significant improvement in standing long jump form, while the control group improved only in jump distance. No significant improvements in running or throwing performance were observed in the intervention group; however, their form scores tended to improve compared with the control group. FIFA 11+K may help enhance movement quality, particularly in jumping tasks, in elementary school boys. These findings suggest its potential as a practical program not only for injury prevention but also for supporting the development of fundamental motor skills in children.